PENGARUH GAYA HIDUP, DESAIN PRODUK, DAN CITRA MEREK TERHADAP MINAT BELI MOTOR MATIC HONDA SCOOPY PRESTIGE PADA MAHASISWA FEB UNESA - Dewi, Tiara Puspita; Rafida, Veni (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
The purpose of this study is to examine the effect of lifestyle, product design and brand image on buying interest in Honda Scoopy Prestige motorbikes for FEB UNESA students. Respondents in this study were FEB UNESA students. The number of respondents in this study were 368 respondents. Sampling was done with purposive sampling technique. This study uses multiple linear regression analysis techniques with SPSS 22.0 as a data analysis tool. Based on the results of data testing conducted, it shows that: 1) Lifestyle has a partial effect on buying interest in Honda Scoopy Prestige on UNESA FEB Students. 2) Product design has a partial effect on buying interest in Honda Scoopy Prestige on UNESA FEB Students. 3) Brand image has a partial effect on buying interest in Honda Scoopy Prestige for UNESA FEB Students. 4) Lifestyle, product design, and brand image simultaneously influence the purchase intention of Honda Scoopy Prestige on UNESA FEB Students.